Consequences of drug binding to immune receptors: Immune stimulation following pharmacological interaction with immune receptors (T-cell receptor for antigen or human leukocyte antigen) with altered peptide-human leukocyte antigen or peptide - Werner J. Pichler (Wolters Kluwer Medknow Publications, 2013)
Drugs may stimulate the immune system by forming hapten-carrier complexes or via their pharmacological features, namely by noncovalent binding to proteins such as immune receptors. The latter type of immune stimulation is called the p-i concept, meaning pharmacological interaction with immune receptors, which implies stimulation of the immune system by noncovalent binding of a drug to T-cell receptors for antigens (p-i TCR) or human leukocyte antigens (p-i HLA). The functional consequences of these interactions are heterogeneous: clinically, it can lead to T-cell mediated reactions such as Stevens-Johnson syndrome/toxic epidermal necrolysis, drug rash with eosinophilia and systemic symptoms, acute generalized exanthematous pustulosis, and maculopapular eruptions. If the drug binds to the TCR, it can become stimulatory, and an additional interaction with HLA/peptide complexes is necessary for full stimulation. The T-cell reaction can be oligoclonal or polyclonal. Binding of drugs to an HLA molecule can have two consequences: if the drug can modify the HLA molecule, a distinct repertoire of peptides might be presented: this is the altered peptide model. However, peptide exchange is not necessary to make the peptide-HLA complex immunogenic: if the drug binds to HLA, already the complex of altered HLA and normal peptide is immunogenic and able to stimulate T-cells (altered peptide-HLA model). The immunological and clinical consequences of different forms of the p-i concept are described with typical p-i binding drugs such as abacavir, carbamazepine, flucloxacillin, allopurinol, and sulfamethoxazole. Thereby the role of drug binding to HLA or TCR, the affinity of drug binding, additional TCR binding, and potential oligoclonality are described and compared.